Seed priming alleviated salinity stress during germination and emergence of wheat (Triticum aestivum L.) - Feghhenabi, Faride; Hadi, Hashem; Khodaverdiloo, Habib; van Genuchten, Martinus Th. [UNESP] (Elsevier, 2020)
Seed priming is known to often alleviate salinity stress during seed emergence and subsequent crop growth. This study compares the effects of salinity stress on the germination and emergence of wheat (Triticum aestivum L.) seeds untreated (control) and primed with ascorbic acid (Asc), potassium silicate (K2SiO3), proline (Pro), spermidine (Spd) and Lake Urmia saline water (LUsw). Saline water from Lake Urmia (Iran) was diluted to produce salinities with electrical conductivities (EC) of 2, 4, 6, 8, 10, 12, 14, 20 dS m−1, while distilled water (EC ≈ 0 dS m−1) was used for the control. Two independent sets of experiments were conducted. The first experiments were used to select the most effective concentration of each priming agent based on the final germination percentage (GP) and germination rate (GR). The second set of experiments aimed to analyze the measured data in terms of salinity response functions in order to quantitatively determine the most effective priming agent(s). The first experiments showed that the most effective concentrations of Spd (0.5 mM), Pro (25 mM), K2SiO3 (1.5 mM) and LUsw (100 mg L−1) mitigated the negative impacts of salinity on GR by 32, 18, 17 and 22 %, respectively. The second experiment showed that the Maas and Hoffman (1977) and van Genuchten and Hoffman (1984) salinity response functions provided effective descriptions of seedling and early growth response to salinity stress. Mean values of the salinity threshold (EC*) and the salinity at which a given trait was reduced by 50 percent (EC50) in these functions were 3.4 and 10.8 dS m−1 for the control, respectively. By comparison, the EC* values for the K2SiO3, Pro, Spd and LUsw primed seeds were 5.3, 4.5, 4.7, and 4.2 dS m−1, respectively, and the EC50 values were 12.4, 11.4, 11.9, and 9.4 dS m−1, respectively. The beneficial effects of K2SiO3 on seedling growth were more evident than those of the other priming agents. K2SiO3 had the highest effect on EC* and EC50 of the vitality index (VI), showing increases of 151 and 34 %, respectively. The highest increases of EC* and EC50 for seedling dry weight (72 and 24 %, respectively) were obtained with Spd and K2SiO3. The findings provide much insight on relieving the negative effects of salinity through cost-effective seed priming operations so as to improve the production of wheat under saline conditions.
Keywords: Emergence; Potassium silicate; Salinity response functions; Seed priming; Seedling